2012
DOI: 10.7598/cst2013.312
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Thermal and Electrical Properties of 2, 2’-HBBF Copolymer Resin

Abstract: Abstract:The copolymer (2, 2'-HBBF) synthesized by the condensation of 2, 2'-dihydroxybiphenyl (2, 2'-HB) and biuret (B) with formaldehyde (F) in the presence of acid catalyst using 1:1:2 molar proportions of the reacting monomers. The thermogravimetric analysis of copolymer resin prepared in the present study has been carried out by non-isothermal thermogravimetric analysis technique in which sample is subjected to condition of continuous increase in temperature at linear rate. The advantage of Freeman-Carrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The first few points that did not fall on straight line were discarded. These types of deviations of points are reported in literature by several research workers [20][21][22][23][24][25][26][27][28][29] .…”
Section: Thermal Study Of Gliclazide-copper Complexmentioning
confidence: 67%
See 1 more Smart Citation
“…The first few points that did not fall on straight line were discarded. These types of deviations of points are reported in literature by several research workers [20][21][22][23][24][25][26][27][28][29] .…”
Section: Thermal Study Of Gliclazide-copper Complexmentioning
confidence: 67%
“…To provide further evidence regarding the degradation system of analyzed compounds, we derived the TG curves by applying an analytical method proposed by Freeman-Carroll 27 and Sharp-Wentworth. 28…”
Section: Theoretical Considerationmentioning
confidence: 99%
“…The high value of activation energies reflects the thermal stability of complex. The entropy of activation is found to have negative values in complex which indicate that decomposition reactions process with lower rate than the normal ones [26,[29][30][31][32][33]. In TGA curve (Figure 7) the initial loss (8.30%) (also given in Tables 4 and 5) is due to two molecules of water of crystallization (70-90 ∘ C) in complex which is in agreement with theoretically calculated percentage of water molecule, that is, 8.70%.…”
Section: Sharp-wentworth Methodsmentioning
confidence: 99%
“…The electrical property of p-cresol and melamine with formaldehyde polymer was measured over a wide range of temperature (313-423 K) 6 . Rahangdale et al 7 carried out the study of terpolymeric resin and found that the electrical conductivity of each of the copolymer resins increases with increase in temperature. Electrical conductivity study has been done of resin synthesized from salicylic acid, butylenediamine and formaldehyde 8 .…”
Section: Introductionmentioning
confidence: 99%